2019
DOI: 10.3390/su11226408
|View full text |Cite
|
Sign up to set email alerts
|

Regional Ethnocentrism on the Food Market as a Pattern of Sustainable Consumption

Abstract: The paper aims to assess the level and predictors of regional ethnocentrism on the market of regional food products in the context of sustainable consumption. The study contributes to the theory of consumer ethnocentrism by extending our knowledge about its regional dimension. Regional ethnocentrism is the preference for products originating from the consumer’s region. I conducted a survey in a representative sample of 1000 inhabitants of Poland with the use of the CAWI (Computer-Assisted Web Interview) method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 53 publications
2
47
1
2
Order By: Relevance
“…The external validity of our findings would surely be enhanced by considering a more representative sample of consumers coming from various regions. Furthermore, the preference for local food products—and, thus, mountain pasture products—could be related to the regional ethnocentrism of consumers [ 89 ], due to the close connection between local traditional practices and regional origin. We tried to measure this connection by classifying the subjects by area of origin, in terms of altitude and degree of urbanization, assuming a closer link for those who lived in a rural or mountain area.…”
Section: Discussionmentioning
confidence: 99%
“…The external validity of our findings would surely be enhanced by considering a more representative sample of consumers coming from various regions. Furthermore, the preference for local food products—and, thus, mountain pasture products—could be related to the regional ethnocentrism of consumers [ 89 ], due to the close connection between local traditional practices and regional origin. We tried to measure this connection by classifying the subjects by area of origin, in terms of altitude and degree of urbanization, assuming a closer link for those who lived in a rural or mountain area.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, during the transition from unwillingness to act to performing the desired behavior, people might be motivated by different benefits associated with the new behavior. Knowing which motives encourage consumers to adopt ecological food consumption patterns could be useful for future campaigns promoting these behaviors [ 30 ]. In the case of Polish urban consumers price incentives and opinions of health specialists would potentially support “greener” consumption behaviors among the currently least engaged parents.…”
Section: Discussionmentioning
confidence: 99%
“…Raising and discussing topics linked to food, health and the environmental protection is one of them. Pro-environmental behaviors include eating local food, so the preference for food products originating from one’s own region (called regional ethnocentrism) may be considered a pattern of sustainable consumption, as its predictors are strongly related to the major pillars of sustainable development [ 30 ]. According to [ 31 ] consumer ethnocentrism is a general tendency acquired during childhood through the process of socialization.…”
Section: Introductionmentioning
confidence: 99%
“…Bryla [68] and Siemieniako et al [69] found the relative importance of elements such as brand image (based on Polish culture and referring to its symbols), local brands as contributors to local identities and the form of their expression, as well as a moral obligation to buy local brands. On the other hand, Bryla [68] and Yagci [70] contributed to the theory of consumer ethnocentrism by providing more insights on its regional dimension in the context of the market of regional food products, where signs of quality are more important for regional ethnocentric consumers; interestingly, this applied not only to regional food, but also conventional food.…”
Section: Literature Reviewmentioning
confidence: 99%